Frequency of Malocclusion of Cleft Lip and/or Palate: A Multicentric Study In Bangladesh - Nazmin, Taskina; Gani, Mohammad Mahfuzul; Jahan, Nasrin; Ruba, Rafat Ara; Pinu, Md Muklesur Rahman (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Objectives: This study aimed to investigate the prevalence of malocclusion based on molar and incisor relationship in a group of Bangladeshi cleft lip and/or palate Patients. Material and Methods: The study was performed on the dental cast and photos of the dentition of 140 individuals with cleft lip and/or palate aged between 5 and 15 years. Convenient sampling was carried out. These were used to study and compare the transverse and frontal occlusion of cleft lip palate subjects. Malocclusion was classified based on Angle’s Molar and British Incisor Classification. Results: The mean age of the subjects was 10.36±3.11 (SD) years. Angle Class III malocclusion (51.42%) was significantly greater than other types of malocclusion. In frontal relation, the incidence of Class I malocclusion was 23.57%. Some subjects had Class II div 1 malocclusion (20%) and Class II div 2 (2.14%). The open bite was more in the anterior segment (2.87%) than the posterior segment (7.93%). On transverse relation, the prevalence of Class III, Class I, Class II malocclusion, and scissor bite was respectively 50%, 21.42%, 18.51%, and 2.14%. Conclusion: Class III malocclusion was the most prevalent followed by class I and class II types of malocclusion in cleft lip and/or palate populations. Cleft lip palate (CLP) subjects demonstrated a higher prevalence of dental malocclusion than normal individuals. J Bangladesh Coll Phys Surg 2025; 43: 122-126